Double head-to-tail direct arylation as a viable strategy towards the synthesis of the aza-analog of dihydrocyclopenta[hi]aceanthrylene – an intriguing antiaromatic heterocycle. Issue 6 (27th November 2015) - Firmansyah, Dikhi; Deperasińska, Irena; Vakuliuk, Olena; Banasiewicz, Marzena; Tasior, Mariusz; Makarewicz, Artur; Cyrański, Michał K.; Kozankiewicz, Bolesław; Gryko, Daniel T.
Abstract : Straightforwardly prepared head-to-tail bis-imidazo[1, 2- a ]pyridine displays antiaromaticity and no fluorescence. Abstract : The first case of double head-to-tail direct arylation of aromatic compounds and the unusual photophysical properties of the resulting 2, 2 a 1, 5 b 1, 7 -tetraazacyclopenta[ hi ]aceanthrylene are reported. This molecule, comprising of two imidazo[1, 2- a ]pyridine units, is antiaromatic due to the changes in the efficiency of π-electron ring current and it belongs to a class of seldom encountered compounds with a dark lowest electronically excited singlet state.